Analisis Kekaburan Norma Penghentian Penuntutan Berdasarkan Keadilan Restoratif dalam Peraturan Kejaksaan Nomor 15 Tahun 2020 dan Implikasinya terhadap Kepastian Hukum - Willhelmin Widya Astuti Fau; I Wayan Empu Guana Pura; Komang Febrinayanti Dantes (Universitas Pendidikan Ganesha, 2026)
Republic of Indonesia Prosecutor's Office Regulation Number 15 of 2020 regulates the termination of prosecution based on restorative justice as an effort to achieve a more restorative-oriented resolution of criminal cases. However, several provisions still contain vague norms that have the potential to lead to differing interpretations and reduce legal certainty. This study aims to analyze the forms of vague norms in Prosecutor's Office Regulation Number 15 of 2020 and their implications for legal certainty. The study uses normative legal methods with a statutory and conceptual approach, supported by a literature review of primary, secondary, and tertiary legal materials. The results indicate that the phrases